INDONESIAN GLOBAL IKHWAN’S RECEPTION AND EXPRESSION TOWARD SUNNAH POLYGAMY IN ONLINE MEDIA - Ahmadi, Rizqa; Hefni, Wildani; Mutrofin, Mutrofin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Evidence of the strength of Indonesian Muslim relations with the text tradition can be found in various practices of daily life. The text referred to in this paper is religious texts, especially hadith. Each group in the community has an expression of diverse receptions to a text. Global Ikhwan, one of the urban Muslim communities in Indonesia which declares the call for polygamy, reveals interesting receptions and expressions to be explored. With a virtual ethnographic approach (netnography), the authors find that they perceive hadith exegesis. The group interpreted the command of polygamy with a more realistic interpretation. They perceive the command of polygamy in the hadith with the meaning of sunnah matrûkah (abandoned sunnah), which is not done by many Muslims. Their expressions are manifested in organizing a short course, coaching for prospective wives who are ready for polygamy, publications, and declarations to various media. If viewed from the aspect of the reception function of the text, the traditions that are receptions are categorized into informative functions, which function as sources of information for carrying out an action.